Comparative Study of Homogeneous Class and Heterogeneous Class of Participation Level and Result Learning in System Reproduction Classes of SMA/MA - Wati, Kharisma Arby Ristiana; Sulistiyawati (Proceeding International Conference on Science and Engineering, 2020)
The study is intended to determine how the differences between classes of homogeneous and class heterogeneous on the level of participation and the results of learning in class XI of the system of reproduction. The research is including field research with the approach of quantitative use study comparisons. Intake sample used technique purposive sampling and using three classes. the class is heterogeneous, class homogeneous male (M) and class heterogenous female (FM). Instruments retrieval of data using the data test multiple choice (posttest) and questionnaire level of participation. Mechanichal analysis of the data using a test statistic one way ANOVA and test Tukey as the test continued. The results of the study indicate that 1) the level of participation in class heterogeneous, class homogeneous male and class homogeneous female is not there differences in views of the value of the significant of 0,122 which means 0,122 > 0,05 and Fcount of 2,185 <Ftable. 2) The result of study on class of heterogenous, class homogeneous male, class homogeneous female there are differences in view on the value of significant of 0,000. Wich means that 0,000 <0.05 and Fcount amounted to 52,657> Ftable, based on test Tukey class that has the value of the results of studying the best is the class of homogeneous male.